1996
DOI: 10.2337/diacare.19.7.726
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Studies on Diabetic Complications Hampered by Differences in GHb Measurements

Abstract: There were large differences in GHb values among laboratories participating in studies of diabetic complications. The present data offer a guide to the comparison of results from the studies and underscores the need for standardization of GHb measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 6 publications
3
37
0
Order By: Relevance
“…It is difficult to compare different levels of HbA 1c since the HbA 1c methods are not yet comparable between countries. Sweden uses the European standard, which, compared with the DCCT standard, is ϳ12% lower (29). The mean weighted HbA 1c level of 7.3% among our patients is the same level as the median HbA 1c level of ϳ10,000 young adult Swedish patients with type 1 diabetes according to the National Diabetes Registry of Sweden (30).…”
Section: Development Of Retinopathymentioning
confidence: 73%
“…It is difficult to compare different levels of HbA 1c since the HbA 1c methods are not yet comparable between countries. Sweden uses the European standard, which, compared with the DCCT standard, is ϳ12% lower (29). The mean weighted HbA 1c level of 7.3% among our patients is the same level as the median HbA 1c level of ϳ10,000 young adult Swedish patients with type 1 diabetes according to the National Diabetes Registry of Sweden (30).…”
Section: Development Of Retinopathymentioning
confidence: 73%
“…The HbA 1c method changed during the follow-up period, but we were able to use conversion formulas to compensate for HbA 1c analysis using different methods. As described above, the methods were, even in the early stages, of high precision and standardized against a national standard and also compared with the NGSP values (16,17). This makes it possible to compare our results with the recommendation of HbA 1c targets after the DCCT study.…”
Section: Discussionmentioning
confidence: 98%
“…A comparison with other laboratories, including the Diabetes Control and Complications Trial (DCCT), has been reported by our group (17).…”
Section: Biochemical Analysismentioning
confidence: 93%